ASSISTANCE AND TRAINING IN CREATING PACKAGING DESIGN TO INCREASE PRODUCT SALES - Rudi Santoso; Darwin Yuwono Riyanto (Universitas Airlangga, 2023)
This activity is to assist New Entrepreneurial MSMEs entering Semester 2 under the auspices of the Sidoarjo Regency Cooperatives and UMKM (Dinkop & UMKM) Service. Training uses the Technical Guidance (Bimtek) model for 5 (five) days. Participants consisted of 100 WUBs throughout Sidoarjo Regency who were engaged in the Food and Beverage (F&B) sector. The method used in this technical guidance uses 5 (five) stages consisting of user research, prototype design, design trials, packaging design and cost efficiency, as well as implementation and evaluation. The indicator for the success of this activity uses before and after measurements using a scale of 0–100 percent. Technical guidance participants are given tests before and after training to determine their progress in absorbing the material. The results of the Technical Guidance evaluation show an average increase in participant competency of 40% starting from user research to design implementation. Based on the results of the learning evaluation and participant enthusiasm, this activity can be continued with further Technical Guidance to strengthen the competence of business actors who are members of WUB under the auspices of Dinkop & UMKM. Apart from that, the reach of participants can be widened to the entire East Java region.